Associação entre condições demográficas e socioeconômicas com a prática de exercícios e aptidão física em participantes de projetos comunitários com idade acima de 50 anos em Ribeirão Preto, São Paulo - Trapé, Átila Alexandre; Marques, Renato Francisco Rodrigues; Lizzi, Elisângela Aparecida Da Silva; Yoshimura, Fernando Eidi; Franco, Laercio Joel; Zago, Anderson Saranz (Associação Brasileira de Saúde Coletiva, 2017)
ABSTRACT:Objective:To investigate the association between both demographic and socioeconomic conditions with physical fitness and regular practice of physical exercises in participants of community projects, supervised by a physical education teacher. This enabled to investigate whether the adoption of an active lifestyle depends only on the personal choice or has any influence of socioeconomic factors.Methods:213 individuals aged over 50 years joined the study, and provided information about their socioeconomic status (age, gender, education/years of study, and income); usual level of physical activity (ULPA); and physical fitness, by a physical battery tests which allowed the calculation of general functional fitness index (GFFI).Results:The generalized linear model showed that participants ranked in the highest GFFI groups (good and very good) had more years of study and higher income (p < 0.05). The multiple linear regression model complements the previous analysis, demonstrating the magnitude of the change in the GFFI in association with the years of study (group > 15), income (all groups) and age (p < 0.05). By means of analysis of variance, a difference between the groups was verified and longer practice of exercises (> 6 months) were also associated with education and income (p < 0.05); among the groups with exercise practice whether greater than or equal to six months, that supervised showed better results in the GFFI (p < 0.05).Conclusion:The association between variables strengthens the hypothesis that adherence and maintenance of physical exercise might not be only dependent of individual’s choice, but also the socioeconomic factors, which can influence the choice for any active lifestyle.

RESUMO:Objetivo:Verificar a associação entre condições demográficas e socioeconômicas com a aptidão física e a prática regular de exercícios físicos supervisionados em participantes de projetos comunitários, possibilitando investigar se a adoção de um estilo de vida ativo depende apenas da escolha pessoal ou sofre influência de fatores socioeconômicos.Métodos:213 indivíduos com idades acima de 50 anos com informações sobre condição socioeconômica (idade, sexo, escolaridade/anos de estudos e renda); nível habitual de atividade física; e aptidão física por meio de testes motores que permitiram o cálculo do Índice de Aptidão Funcional Geral (IAFG).Resultados:O modelo linear generalizado de comparação de grupos evidenciou que os participantes classificados nos grupos de IAFG mais elevado (bom e muito bom) apresentaram maiores escolaridade e renda (p < 0,05). O modelo de regressão linear complementa a análise anterior, evidenciando a magnitude da modificação da pontuação do IAFG na associação com os anos de estudos (grupo ≥ 15), a renda (todos os grupos) e a idade (p < 0,05). Pela Análise de Variância, verificou-se diferença entre os grupos e, com isso, associação entre maior tempo de prática de exercícios (> 6 meses) com a escolaridade e a renda; entre os grupos com prática de exercícios igual ou superior a seis meses, o grupo supervisionado apresentou os melhores resultados no IAFG (p < 0,05).Conclusão:A associação entre as variáveis fortalece a hipótese de que a adesão e manutenção da prática de exercícios podem não ser dependentes apenas da escolha do indivíduo, mas também de fatores socioeconômicos que podem influenciar a escolha pelo estilo de vida ativo.
Association between demographic and socioeconomic conditions with exercise practice and physical fitness in community projects participants aged 50 years or more in Ribeirão Preto, São Paulo
Keywords: Aging; Educational status; Life style; Exercise; Income; Physical inactivity; Sedentary lifestyle; Envelhecimento; Escolaridade; Estilo de vida; Exercício; Renda; Estilo de vida sedentário